PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN KECERDASAN SPIRITUAL TERHADAP KINERJA WIRAUSAHA MUSLIM DI KABUPATEN PURWAKARTA - Ismail Ludin; H. Suherman Saleh; Dedeng Abdul Gani Amruloh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2018)
Islam is a comprehensive religion. Islam is not only discussing about the dimension of ukhrowi (hereafter) but also world. One of that dimension is practicing of entrepreneur. Practicing of entrepreneur is one of the way to get a performance’s successful. In Islamic perspective, the success of muslimpreneur performance is associated in word of Al falah. Al falah is a success concept for muslimpreneur in the world and hereafter. There are many factors that affect the success of muslimpreneur performance. Human intelligent as the main factor surrounding of that. According to the phenomenon, this research aims to examine the effect of intellectual, emotional, and spiritual quotient toward the muslimpreneur performance. This research used descriptive analityc method. The population of this research is the Islamic small entreprise in Purwakarta regent with 86 number of samples. Double-linier-regression is used as analysis instrument. Library and field research as the dimension of research through questionnaire. The result of this research indicates first, partially, the muslimpreneur performance is insignificantly affected by intellectual and emotional quotient variable. Only the spiritual quotient that significantly affects toward the muslimpreneur perfomance. Second, simultanously, the muslimpreneur performance is significantly affected by the variable of intellectual, emotional, and spiritual quotient. This research is limited in independend variable. Exploring the most essential independen variable should be done in order to get better result. Keywords : Intelellectul quotient, emotional quotient, spiritual quotient, muslimpreneur performance, and Al falah.